The updated duplex fluorescence quantitative RT-PCR assay for simultaneous detection of PRRSV-1 and PRRSV-2 - Xiaoxiao Tian; Haojie Wang; Zeqing Liu; Ziyi Wei; Yongbo Yang; Haiwei Wang; Guoqing Liu; Hao Song; Xinyi Huang; Tongqing An; Tongqing An (Frontiers in Cellular and Infection Microbiology)
IntroductionPorcine reproductive and respiratory syndrome (PRRS) is one of the most economically devastating infectious diseases in the global swine industry. With the continuous mutation and recombination of PRRSV, existing detection methods frequently result in false negatives, further complicating the prevention and control of PRRS.MethodsThe duplex real-time quantitative RT-PCR (RT-qPCR) for the simultaneous detection of PRRSV-1 and PRRSV-2 was developed by designing specific primers and probes based on the ORF6 gene, which is different from conventional nucleic acid detection methods that are typically based on the ORF7 gene.ResultsThe method showed high specificity for exclusively detecting PRRSV-1 and PRRSV-2, with no cross-reactivity observed against other porcine pathogens. The limit of detection (LOD) was 8.42 copies for PRRSV-1 and 7.84 copies for PRRSV-2. Intra-assay coefficients of variation (CVs) were 0.22–1.07% and inter-assay CVs were 0.52–1.28%. A total of 356 clinical samples were detected using the developed duplex RT-qPCR and compared to the WOAH-recommended RT-qPCR assay and commercial universal PRRSV RT-qPCR detection kit. The assay established in this study demonstrated higher positivity rates, indicating its superior sensitivity.DiscussionAn efficient, sensitive, and accurate method for the detection and differentiation of PRRSV-1 and PRRSV-2 was developed and applied to the detection and monitoring of PRRSV.